ESTIMATION OF TEA LEAVES MASS TRANSFER PARAMETERS UNDERGOING MICROWAVE HEAT TREATMENT - Demirhan, E.; Sert, G.; Harmanli, S. H.; Ozbek, B. (PLAPIQUI(UNS-CONICET), 2018)
In the present study, tea leaves (Camellia sinensis) were dried in the domestic microwave oven in order to determine the effect of microwave output power and sample amount on moisture ratio, drying time and effective moisture diffusivity. Five different microwave output power (180-900 W) and five different sample amount (20-100 g) values were used in the drying experiments. The drying data were fitted to some empirical and semi empirical models in order to determine the kinetic parameters. Among of the models proposed, the Page model gave a better fit for all drying conditions applied. The effective moisture diffusivity values were calculated by using the method of slopes at various microwave output powers and sample amounts. Moreover, the activation energy was calculated using an exponential expression based on Arrhenius equation.
Keywords: Microwave drying; Tea leaves; Drying kinetics; Activation energy; Effective moisture diffusivity; LAYER DRYING CHARACTERISTICS; CELERY LEAVES; KINETICS; AIR; POMACE; COLOR; Engineering